2016
DOI: 10.17159/sajs.2016/20150316
|View full text |Cite
|
Sign up to set email alerts
|

Archiving South African digital research data: How ready are we?

Abstract: Digital data archiving and research data management have become increasingly important for institutions in South Africa, particularly after the announcement by the National Research Foundation, one of the principal South African academic research funders, recommending these actions for the research that they fund. A case study undertaken during the latter half of 2014, among the biological sciences researchers at a South African university, explored the state of data management and archiving at this institutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 16 publications
0
22
0
Order By: Relevance
“…Despite this, there is currently scant evidence of the willingness, extent, concerns and practices of sharing data by South African researchers (Patterton et al 2018). The few studies conducted in South Africa in this area focus on data sharing practices of certain disciplines (Koopman & de Jager 2016). The current study has a broader aim.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…Despite this, there is currently scant evidence of the willingness, extent, concerns and practices of sharing data by South African researchers (Patterton et al 2018). The few studies conducted in South Africa in this area focus on data sharing practices of certain disciplines (Koopman & de Jager 2016). The current study has a broader aim.…”
Section: Introductionmentioning
confidence: 92%
“…However, data sharing is not only about publishing the research data for easy access. Several studies have shown that sharing research data via emails and portable devices such as memory sticks or CDs is still practiced (Wiley 2014;Koopman & De Jager 2016;JISC, 2016). This caused Michener (2015) to simple define data sharing as the practice of making one's research data available or accessible for use by others.…”
Section: What Is Research Data?mentioning
confidence: 99%
See 1 more Smart Citation
“…The general subject of scientific data archiving/sharing/ publication has been addressed. 9,[13][14][15] The Global Biodiversity Information Facility (GBIF) currently publishes just over 1 billion standardised biodiversity occurrence records, from about 39 000 data sets contributed by about 1000 data providers around the world (Figure 2). Of these, 77% are records of human observations, and only 15% are records of physical specimens.…”
Section: Box 1: Data Publicationmentioning
confidence: 99%
“…The survey data is based on a survey of more than 500 scientists from more than 50 leading research universities in the US, Canada, Britain, Australia, New Zealand, and Ireland. In work (Koopman, & de Jager, 2016), the features of storing and managing digital data on the example of institutions in South Africa have been explored. It turned out that, although some researchers were already engaged in digital archival data in storage facilities, neither researchers nor universities carried out systematic management of research data.…”
Section: Literature Reviewmentioning
confidence: 99%